2022
DOI: 10.1002/app.52520
|View full text |Cite
|
Sign up to set email alerts
|

A green composite hydrogel based on xylan and lignin with adjustable mechanical properties, high swelling, excellent UV shielding, and antioxidation properties

Abstract: This study successfully prepared a novel green composite hydrogel based on carboxymethyl xylan and lignin with adjustable mechanical properties, high swelling, excellent UV shielding, and antioxidation performance. The structure and morphology of the hydrogel were characterized by Fourier transform infrared spectra, scanning electron microscopy, thermogravimetric analysis, rheological analysis, and swelling ratio. Results showed that lignin could significantly improve the mechanical properties of composite hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
3
0
1
Order By: Relevance
“…This is due to the fact that stronger crosslinking of the SF/MXene hydrogel not only weakens the ability to absorb water but also enhances its mechanical strength. Such a phenomenon is also commonly observed in other hydrogels [39,40].…”
Section: Resultssupporting
confidence: 71%
“…This is due to the fact that stronger crosslinking of the SF/MXene hydrogel not only weakens the ability to absorb water but also enhances its mechanical strength. Such a phenomenon is also commonly observed in other hydrogels [39,40].…”
Section: Resultssupporting
confidence: 71%
“…Slower thermal degradation is observed for PP-pine pellets, resulting in a 28% mass loss, while PPflax pellets lose 13% mass. A recent study indicated an enhancement in the thermal stability of PAM and CMX hydrogels following the introduction of lignin [22]. For the third stage (up to 600°C), additional losses of 12% for flax fibre and 8% for pine fibre are noted.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…utilizaram nanofibras de carbono derivada de lignina alcalina na produção de eletrocatalisador livre de metal. Yi et al; adicionaram lignina a um hidrogel a base de carboximetil xilano e notaram que sua presença melhorou as propriedades mecânicas do hidrogel, como tensão de compressão e tenacidade.…”
Section: Licor Negro (Subproduto)unclassified